Perinatal renal venous thrombosis: presenting renal length predicts outcome. Issue 4 (7th February 2006) - Winyard, P J D; Bharucha, T; De Bruyn, R; Dillon, M J; van't Hoff, W; Trompeter, R S; Liesner, R; Wade, A; Rees, L
Abstract : Background: Renal venous thrombosis (RVT) is the most common form of venous thrombosis in neonates, causing both acute and long term kidney dysfunction. Historical predisposing factors include dehydration, maternal diabetes, and umbilical catheters, but recent reports highlight associations with prothrombotic abnormalities. Study: Twenty three patients with neonatal RVT were analysed over 15 years. Predisposing factors, presentation, and procoagulant status were compared with renal outcome using multilevel modelling. Results: Median presentation was on day 1: 19/23 (83%) had pre/perinatal problems, including fetal distress (14), intrauterine growth retardation (five), and pre-identified renal abnormalities (two); 8/18 (44%) had procoagulant abnormalities, particularly factor V Leiden mutations (4/18). Long term abnormalities were detected in 28/34 (82%) affected kidneys; mean glomerular filtration rate was 93.6 versus 70.2 ml/min/1.73 m 2 in unilateral versus bilateral cases (difference 23.4; 95% confidence interval 6.4 to 40.4; p = 0.01). No correlation was observed between procoagulant tendencies and outcome, but presenting renal length had a significant negative correlation: mean fall in estimated single kidney glomerular filtration rate was 3 ml/min/1.73 m 2 (95% confidence interval 3.7 to −2.2; p = 0.001) per 1 mm increase, and kidneys larger than 6 cm at presentation never had a normal outcome. Conclusions: This subgroup of neonatal RVT would be better termed perinatal RVT to reflect antenatal and birth related antecedents. Prothrombotic defects should be considered in all patients with perinatal RVT. Kidney length at presentation correlated negatively with renal outcome. The latter, novel observation raises the question of whether larger organs should be treated more aggressively in future.